The Magdalene in the Reformation - Arnold, Margaret (The Belknap Press of Harvard University Press, 2018)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Introduction. A Woman for All Seasons -- 1. The Medieval Magdalene: Establishing a Cult of Personality -- 2. Teacher of the Dear Apostles: Lutheran Preaching on Mary Magdalene -- 3. Publish the Coming of the Lord: Evangelical Magdalenes -- 4. A Most Holy Penitent: Preaching and Teaching the Magdalene in the Catholic Reformation -- 5. Love Made Her Dare: The Magdalene among Catholic Women -- 6. These Magdalens: Diversity in the Reformed Tradition -- 7. Mark This, Ye Despisers of the Weakness of Women: The Magdalene of the Radical Reformation -- Conclusion. An Army of Such Ladies -- Notes -- Acknowledgments -- Index